Composition and Comprehensive Evaluation of Free Amino Acids in Different Brassica campestris Cultivars - Kai ZHU; Zhuoyi DING; Yifei WU; Zhiquan LIU; Xiaoquan DUAN; Zhuqing ZHANG; Wenchao CHEN; Luyan LIAO; Xiaobo ZHOU (Shipin gongye ke-ji)
This study aimed to evaluate the differences in the overall quality of free amino acid (FAA) in different varieties of Brassica campestris. The types and contents of FAA were detected by high performance liquid chromatography (HPLC), and the FAA compositions of the 16 Brassica campestris cultivars were evaluated by taste activity value (TAV), correlation analysis (CA), principal component analysis (PCA) and hierarchical cluster analysis (HCA). Results showed that there were 22~23 FAA in 16 kinds of Brassica campestris, among which citrulline (Cit) was not detected in some varieties. The total free amino acid (TFAA) content of Brassica campestris was in the range of 1.30~6.77 mg/g, with the highest TFAA content in XT-3 and the lowest in CT-4. The TAV results showed that umami amino acids were the main flavor amino acids, and glutamine (Gln) and glutamic acid (Glu) were the main contributing amino acids. The medicinal amino acids were abundant, with the contents range of 0.34~1.95 mg/g. The correlation between the FAA of different Brassica campestris varieties was excellent, while the correlation between the FAA of glycine (Gly) and cysteine (Cys) was only positively significant (P<0.01). Four principal components were extracted using PCA, with a cumulative variance contribution rate of 87.022%, which could effectively analyze all the FAA information characteristics. The HCA results were consistent with the PCA, and the 16 Brassica campestris cultivars were categorized into 3 major groups. The top 3 varieties ranked by the comprehensive evaluation were XT-3, XT-4 and ZM-2, respectively. These results could effectively reflect the differences between the FAA of different germplasm of Brassica campestris, and provide some theoretical basis for idioplasmic selection and product development of Brassica campestris.